A Note on the New Ostrowski and Hadamard Type Inequalities via the Hölder–İşcan Inequality - Çetin Yildiz; Juan E. Nápoles Valdés; Luminiţa-Ioana Cotîrlă (Axioms, 2023)
For all convex functions, the Hermite–Hadamard inequality is already well known in convex analysis. In this regard, Hermite–Hadamard and Ostrowski type inequalities were obtained using exponential type convex functions in this work. In addition, new generalizations were found for different values of <semantics>θ</semantics>. In conclusion, we believe that our work’s technique will inspire more study in this field.